Envolvimento dos sistemas purinérgico, colinérgico e estresse oxidativo nos distúrbios da tireoide: possível efeito protetor da quercetina - Baldissarelli, Jucimara (2017)
Thyroid hormones modulate the metabolic pathways in the body and have important physiological functions in the brain and vascular system. Changes in their production or distribution lead to disorders such as hypothyroidism and hyperthyroidism, which are related to modifications in endothelial function, contributing to a higher incidence of vascular diseases, besides being related to reactive oxygen species production (ROS). Moreover, in the Central Nervous System (CNS), the involvement of purinergic and cholinergic systems in thyroid disorders has been gaining significance. Adenosine triphosphate (ATP) and acetylcholine (ACh) are extracellular signaling molecules in the CNS and other tissues that upon release are degraded by the action of ectonucleotidases and acetylcholinesterase (AChE), respectively. Together with the ATP, ADP, AMP and adenosine (Ado) regulate physiological processes such as platelet aggregation and vascular tone. In this context, the objective of this study was to evaluate the effect of quercetin on ectonucleotidase and AChE activities in the synaptosomes of the cerebral cortex of rats with hypothyroidism. Moreover, to evaluate the activity and expression of ectonucleotidases in platelets and biomarkers of oxidative stress in experimental model of hypothyroidism and hyperthyroidism and in patients with post thyroidectomy hypothyroidism. Hypothyroidism and hyperthyroidism in animal models were induced by administration of methimazole or L-Thyroxine, respectively, for 30 days. Treatment with quercetin 10 or 25 mg/kg started after that the hypothyroidism induction was confirmed and followed for 60 days. Patient collections were performed approximately 45 days after thyroidectomy. The results demonstrated that hypothyroidism caused a decrease in AChE activity in synaptosomes of cerebral cortex and quercetin treatment maintained this activity decreased. In vitro tests confirmed the inhibition of AChE proportional to the quercetin’s dose tested, suggesting that quercetin could be used as adjuvant in the treatment of neurological disorders. NTPDase activity was not altered in hypothyroidism, but the hydrolysis of AMP by ecto-5'-nucleotidase (E-5'-NT) increased. Treatment with quercetin caused a decrease in the activities of NTPDase, E-5'-NT and adenosine deaminase (ADA), which could contribute to moderately increased levels of Ado in the CNS. As Ado acts as a neuroprotective molecule this may be one of the mechanisms by which quercetin exerts its beneficial effects on the CNS. The results found in platelets showed a decrease in the activities of NTPDase and E-5'-NT and an increase in ATP, ADP and AMP levels in animals with hyperthyroidism. However, Ado levels were lower, which can be attributed to the reduced 5'-NT and increased ADA activities. Animals with hypothyroidism showed only a decrease in E-5'-NT activity and an increase in AMP levels, which may be due to the greater hydrolysis of ATP to AMP by echnophosphatase/ phosphodiesterase (NPP), which increased in both groups. In the third work of this thesis, the results showed an increase in the activities of the enzymes of the purinergic system in patients with hypothyroidism. In addition, the expression of NTPDase 1 (CD39) was also higher, indicating that the impact of thyroid removal may cause important changes at the molecular level. Ado levels were lower in patients and ADA activity was increased. We also observed changes in redox parameters such as: increased ROS production, lipid peroxidation, protein carbonylation, T-SH, NPSH and ascorbic acid levels, as well as decreased GST activity. We suggest with these results that the oxidative stress presented by patients is related to the increase in the activity of the ectonucleotidases and the ADA, which was demonstrated by the positive correlation between the ROS production and the enzymatic activities. Finally, the presented results can help to understand the metabolic alterations that occur in thyroid disorders, with the involvement of the purinergic and cholinergic system and of the oxidative stress, and to seek therapies that prevent the aggravation of the diseases.